Status of Women as Citizen in the Paradigm of Inclusive Citizenship - Baiq L.S.W. Wardhani (Jurnal Perempuan, 2014)
Political arena has witnessed the masculinization of women’s role in the public. The tendency to give the public to men has made women unable to express their ideas in full engagement as equal citizen. Involving back women into the discourse of the state is a form of defeating the myth that women are irresponsible citizens. Irresponsibility of women is the reversal effect of political exclusion of female’s voices under the regimentation of male-based polity. This paper will investigate the status of women specifically under the paradigm of active and inclusive citizenship.